2010
DOI: 10.1016/j.devcel.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Gradients of a Ubiquitin E3 Ligase Inhibitor and a Caspase Inhibitor Determine Differentiation or Death in Spermatids

Abstract: Caspases are executioners of apoptosis but also participate in a variety of vital cellular processes. Here, we identified Soti, an inhibitor of the Cullin-3-based E3 ubiquitin ligase complex required for caspase activation during Drosophila spermatid terminal differentiation (individualization). We further provide evidence that the giant inhibitor of apoptosis-like protein dBruce is a target for the Cullin-3-based complex, and that Soti competes with dBruce for binding to Klhl10, the E3 substrate recruitment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 54 publications
(68 reference statements)
5
95
2
Order By: Relevance
“…Relative to other insects, there is a greater number of desaturase genes in ants 62 , although alkenes or polyunsaturated alkenes have not been found in all ants investigated 63 . Z. nevadensis nuttingi displays two alkadienes and two alkatrienes in the cuticular profile of reproductive individuals 49 , but the number of desaturases is at the lower end of the number of putatively functional desaturase genes found in ants (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). If the desaturase genes are linked to more complex communication, we predict that an expansion of desaturase genes should be found in higher termites as we also predicted for genes associated with olfactory perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to other insects, there is a greater number of desaturase genes in ants 62 , although alkenes or polyunsaturated alkenes have not been found in all ants investigated 63 . Z. nevadensis nuttingi displays two alkadienes and two alkatrienes in the cuticular profile of reproductive individuals 49 , but the number of desaturases is at the lower end of the number of putatively functional desaturase genes found in ants (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). If the desaturase genes are linked to more complex communication, we predict that an expansion of desaturase genes should be found in higher termites as we also predicted for genes associated with olfactory perception.…”
Section: Discussionmentioning
confidence: 99%
“…Of the gene families that underwent significant expansion in Z. nevadensis, four exhibit a significant male-specific overexpression and have putative associations with male spermatogenesis or cell division ( 19,20 . Alpha-tubulins interact with SINA during cell division 21 while the human homologue to SINA binds a member of the polycystin (PKD) genes that are regularly expressed in testes 22,23 .…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila melanogaster, tightly controlled spatial regulation of effector caspase activity is crucial during the terminal differentiation of spermatids, a process also known as individualization (Kaplan et al 2010). Kaplan and colleagues have shown that a spermatid contains a distal-to-proximal gradient of the protein Soti, which results in a similar directional gradient of the IAP dBruce (because Soti inhibits an E3 ubiquitin ligase that ubiquitylates dBruce).…”
Section: Caspase Regulation In Nonapoptotic Cellular Processesmentioning
confidence: 99%
“…This may not come as a surprise, as the process of apoptosis itself is associated with extensive cytoskeletal and morphological changes of the doomed cell. To give a few examples for such CDPs, caspases were reported to promote major changes in cell morphology during dendritic pruning in some of the Drosophila sensory neurons (Figures 2a-d), 7 the cytoplasmic extrusion during spermatid terminal differentiation in Drosophila (Figure 2i) 8,9 and during nuclear extrusion in mammalian red blood cells (Figure 2l). 10 Another emerging feature of CDPs is the multiple functions of caspases in modulating learning, memory and behavior by shaping neurons and affecting neurite remodeling and synaptic plasticity (Figures 2a-d, g and h).…”
mentioning
confidence: 99%
“…13 In terminally differentiating Drosophila spermatids, caspase activation is coordinated with the gradual extrusion of the bulk cytoplasmic contents, such that a ubiquitin ligase complex (CRL3) gradually activates caspases in the same direction throughout the 2 mm long elongated cell (Figure 2i). 9 Furthermore, activation of caspases by the CRL3 complex is limited to the surface of the two elongated spermatid mitochondria, thus further reducing the rate of caspase activation throughout these cells (Figure 2j). 8 Low and transient caspase activity levels were also reported for other CDPs.…”
mentioning
confidence: 99%